Firefly luciferase inhibition - João M. M. Leitão (2010)
Firefly luciferase (Luc) is the most studied of the luciferase enzymes and the mechanism and kinetics of the reactions catalyzed by this enzyme have been relatively well characterized. Luc catalyzes the bioluminescent reaction involving firefly luciferin (D-LH2), adenosine triphosphate (ATP), magnesium ion and molecular oxygen with the formation of an electronically excited species (oxyluciferin), inorganic pyrophosphate (PPi), carbon dioxide and adenosine monophosphate (AMP). Luc also catalyzes other nonluminescent reactions, which can interfere with the light production mechanism. Following electronic relaxation, the excited oxyluciferin emits radiation in the visible region of the electromagnetic spectrum (550-570 nm). Among the various possible compounds, several classes of inhibitory substances interfere with the activity of this enzyme: here, we consider substrate-related compounds, intermediates or products of the Luc catalyzed reactions, in addition to anesthetics and, fatty acids. This review summarizes the main inhibitors of Luc and the corresponding inhibition kinetic parameters.